Proteoform Profiles Reveal That Alpha-1-Antitrypsin in Human Serum and Milk Is Derived From a Common Source - Jager, Shelley; Cramer, Dario A. T.; Hoek, Max; Mokiem, Nadia J.; van Keulen, Britt J.; van Goudoever, Johannes B.; Dingess, Kelly A.; Heck, Albert J. R. (Frontiers in Molecular Biosciences, 2022)
The Alpha-1-Antitrypsin (A1AT) protein is an important protease inhibitor highly abundant in human serum and other body fluids. Additional to functioning as a protease inhibitor, A1AT is an important acute phase protein. Here, we set out to compare the proteoform profiles of A1AT purified from the human serum and milk of eight healthy donors to determine the origin of human milk A1AT. Following affinity purification, size-exclusion chromatography coupled to native mass spectrometry was used to monitor individual proteoform profiles comparing inter- and intra-donor profiles. The A1AT intra-donor proteoform profiles were found to be highly identical between serum and milk, while they were highly distinct between donors, even when comparing only serum or milk samples. The observed inter-donor proteoform variability was due to differences in the abundances of different N-glycoforms, mainly due to branching, fucosylation, and the relative abundance of N-terminally processed A1AT fragments. From our data we conclude that nearly all A1AT in serum and milk is synthesized by a common source, i.e. the liver, and then secreted into the circulation and enters the mammary gland via diffusion or transport. Thereby, proteoform profile changes, as seen upon infection and/or inflammation in the blood will be reflected in the milk, which may then be transferred to the breastfed infant.